2014
DOI: 10.1007/s10869-014-9384-3
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Method, Motivation, and Empathy on Diversity Training Effectiveness

Abstract: Purpose The purpose of this paper is to examine method, motivation, and individual difference variables as they impact the effectiveness of a diversity training program in a field setting. Design We conducted a longitudinal field experiment in which participants (N = 118) were randomly assigned to participate in one of three diversity training methods (perspective taking vs. goal setting vs. stereotype discrediting). Eight months after training, dependent measures on diversity-related motivations, attitudes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 40 publications
4
76
0
Order By: Relevance
“…This occurs when authors define empathy narrowly as one of the dimensions of empathy (or as sympathy), and then define another dimension of empathy as a different construct. For example, Lindsey, King, Hebl, and Levine () defined empathy as “the capacity to understand others' emotions and experiences” (p. 609) and then included a separate definition (and measurement) of perspective taking. Similarly, Longmire and Harrison () conducted a meta‐analysis to differentiate perspective taking from empathy (operationalized as empathic concern).…”
Section: Critical Review Of Empathy Research In Organizational Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…This occurs when authors define empathy narrowly as one of the dimensions of empathy (or as sympathy), and then define another dimension of empathy as a different construct. For example, Lindsey, King, Hebl, and Levine () defined empathy as “the capacity to understand others' emotions and experiences” (p. 609) and then included a separate definition (and measurement) of perspective taking. Similarly, Longmire and Harrison () conducted a meta‐analysis to differentiate perspective taking from empathy (operationalized as empathic concern).…”
Section: Critical Review Of Empathy Research In Organizational Behaviormentioning
confidence: 99%
“…For example, Riess et al () implemented an empathy intervention for resident physicians that focused on increasing awareness of empathy and improving skills associated with cognitive empathy (i.e., emotion recognition) and behavioral empathy (i.e., verbal and behavioral responses). Lindsey et al () manipulated perspective taking by asking college students to write a narrative about a day in the life of a member of a marginalized group. Organizational researchers should consider adapting such existing interventions and/or developing new interventions that align with a multidimensional conceptualization of empathy for implementation in field settings.…”
Section: Critical Review Of Empathy Research In Organizational Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal evaluation of diversity training effectiveness in a general student sample found that dispositional empathy moderated the effect of perspective-taking training on attitudes and supportive behaviors toward gay and African American individuals, such that the training only benefitted students who were low in dispositional empathy prior to the intervention (Lindsey et al, 2015). However, to our knowledge, the moderating role of participant characteristics on training effectiveness has not been tested in the context of medical education.…”
Section: Introductionmentioning
confidence: 99%